Slope, y-intercept, equation, standard form??? HELP?? =( I seriously don't understand!!!??
The point slope form is: y – y1 = m(x – x1) This follows directly from the defintion of slope which is just (y - y1)/(x - x1) The standard form is: Ax + By = C The slope-intercept form is: y = mx + b 1. (6,2, m=1/2) (6,2) is a point on the line and m is the slope. All you do is substitute these values into the standard form: y - 2 =(1/2)x - 6 y - 2 = (1/2)(x - 12) 2. (4,1), (-3,6) In this case you have two points and do not know the slope. Find the slope: y - y1 = m(x - x1) m = (y - y1)/(x - x1) = (6 - 1)/(-3 - 4) = -5/7 Put this value of m back into the standard equation along with either of the points. Using the first point: y - 1 = (-5/7)(x - 4) You can check by putting in the second point. 6 - 1= (-5/7)(-3 -4) = 5 which is right 3. (1,5), m=0 This is a special case since the slope is 0. This is just a line parallel to the x-axis. You end up with y - y1 = 0 so: y = 5 4.(-2,5), (9,5) Again this is two points. Follow the same procedure that was used for 2. Find the slope: m = (5 - 5)/(9 - (-2)) = 0/11 = 0 This is another line parallel to the x-axis so: y = 5 You can also tell by inspection since the y value is the same for both points. 5. (-5,7), (0, 1/2) First find the slope: m = (1/2 - 7)/(0 - (-5)) = (-13/2)/5 = -13/10 Using this and the first point in the point-slope form: y - 7 = (-13/10)(x - (-5)) = (-13/10)(x + 5) y - 7 = (-13/10)x - 13/2 y + (13/10)x = 1/2 Check by putting in the second point: 1/2 + (13/10)(0) = 1/2 which is right 6. m=-3, b=0 Slope intercept form is: y = -3x + 0 so: y = -3x 7. x=2y -7 The slope and y intercept can be found by changing the form of the equation to slope-intercelt (y = mx + b) 2y = x + 7 y = (1/2)x + 7/2 So slope = 1/2 and y intercept is 7/2 8. 1/2x+1/4y=3 Do as in 7. (1/4)y = (-1/2)x + 3 y = -2x + 12 So slope is -2 and y intercept is 12 9. 5x1/2y=2 do you mean (5x)[(1/2)y] = 2 ???? or 5x[1/(2y)] = 2 ????? I'm sorry I don't know what you mean here
How to rearange F=ma to A=?
heres an idea which always helps me rearrange equations. a formula triangle. draw out a triangle and then create three boxes inside by drawing a T. In each of the boxes you've created you need to put one of the letters from the equation. The equation you currently have is F= m*a. To rearrange this equation put the m and the a into the bottom boxes and the F above. Because there is a vertical line between the m and the a, this means you times them. If there is a horizonal line between two letters you divide them. So to find a, you must divide F by m. this works for almost any three part equation. more help? just ask =]
Y = mx + c ..... quick help?
What you would do is substitute the co-ordinates (17.5, 3.17) into the equation y = mx +c. You get: 3.17 = 0.08* 17.5 +c Then you rearrange the equation so that c is isolated. 3.17-1.4 =c c= 1.77 Then simply put c = 1.77 into you equation. So..... y = 0.08x + 1.77 Hope this helps!
Intro Calculus (grade/year 11) question. Equations in form: y=mx+c...?
are you trying to get strangers to do your homework? the first questions are all just a matter of basic algebra. 1a) 3x-2y=12 subtract 3x from both sides: -2y=12-3x divide by -2 y=-6+(3/2)x re-arrange y=(3/2)x-6 voila! m=(3/2) b=6 you can do parts b,c,d on your own unless someone else answers them for you. Question 2: the y intercept is where x=0 0/a+y/b=1 y/b=1 multiply by b y=b the x intercept is where y=0 same thing: x/a+0/b=1 x/a=1 multiply by a x=a for the gradient (slope) we need to get into y=mx+b form again just algebra x/a+y/b=1 subtract x/a y/b=1-x/a multiply by b y=b-(b/a)x gradient=b/a Question 3: solve algebraically, 3x-2y=12 2x-5y=19 there's a number of ways to do this, I'm not sure which you are familiar with. My personal favorite is cancellation multiply the first equation by 2 and the second by three to get 6x-4y=24 6x-15y=57 now subtract the two equations: 0x+11y=-33 divide by 11 y=-3 now substitute y=-3 back into one of the equations 3x-2(-3)=12 3x+6=12 subtract 6 3x=6 divide 3 x=2 the solution is x=2, y=-3 Question 4 I'm going to be naughty and not explain myself on these it's late and I'm tired a)(x+5)(x-2) b)(2x-1)(x-3) c)(3x+2)(x-3) ta daa!
PLEEAASSEEE!!! : re-arranging equations to y=mx+c?
x + y = 2*y + 4 Step 1) move all the terms containing a 'y' to the left side. And, move everything else to the other side. y - 2*y = -x + 4 Step 2) Simplify if you can -y = - x + 4 Step 3) Divide everything by whatever is in front of 'y'. In this case, it is a -1 y = x - 4 It is a systematic and mechanical process. You move all the terms containing 'y' to one side and everything else to the other side. What follows should be natural.
Finding the equation of a straight line? Please help :)?
There are two things here that you need to figure out. You have the equation y = mx + b, and you need to figure out the slope (m) and the y-intercept (b) of your perpendicular line. First things first, put the equation of your original line into y = mx + b form. You will get y = 6/7 x + 2/7. You now know the slope of your original line, which is 6/7. Well, you know that the perpendicular line's slope will be the reciprocal of the original line's slope. Therefore, the slope of its perpendicular line is -7/6. Now, you need to figure out the y-intercept of the perpendicular line (b). You already know that the line goes through the points (4, 0). And you know the slope. You can use your y = mx + b equation to figure this out. Input your slope in place of m and the points (4, 0) in place of the y and x in this equation to get 0 = -7/6 * 4 + b. Solve this equation to find that your b is 4.667. Now you have figured out that the y-intercept of your perpendicular line is at (0, 4.667) You have figured out all the variables that you need. Now plug them into your y = mx + b equation, and you will find that the equation to your perpendicular line is: y = -7/6 x + 4.667 In decimal form, it would be y = -1.167x + 4.667. In fraction form, it would be y = -7/6 x + 14/3
I am having a problem with this algebra problem?
Find the x and y intercepts individually. Firstly, the x intercept is where y = 0 so, 2x + 5 = 0 => x = -5/2.....intercept (-5/2, 0) The y intercept is where x = 0 so, -2y + 5 = 0 => y = 5/2......intercept (0, 5/2) You could re-arrange the original equation to get: 2y = 2x + 5 so, y = x + 5/2......in the form y = mx + c, where m is the intercept and c the y intercept. From this we see that the slope or gradient is 1 and the intercepts are as before. :)>
first re arrange the formula.. in the form y = mx + c 4x + 3y = -6 4x + 6 = -3y -3y = 4x + 6 y = -4/3*x - 2 m is the gradient of the line which is -4/3 the gradient of the perpendicular line multiplied by the gradient of the actual line will give and answer of -1. Therefore let a = the gradient of new line.. -4/3 * a = -1 a = -1 * -3/4 a = 3/4 therefore the gradient of the perpendicular line is 3/4 now put it into the equation y = mx + c .. y = (3/4)*x + c we don't know "c" but we know the values of "x" and "y".. so put it into the above equation 1 = (3/4)*2 + c 1 = 6/4 + c 1 = 1.5 + c 1 - 1.5 = c -0.5 = c c = -0.5 therefore the equation of the perpendicular line is: y = (3/4)*x - 0.5